The entomological impact of passive metofluthrin emanators against indoor Aedes aegypti: A randomized field trial. - Gregor J Devine; Gonzalo M Vazquez-Prokopec; Wilbert Bibiano-Marín; Norma Pavia-Ruz; Azael Che-Mendoza; Anuar Medina-Barreiro; Josue Villegas; Gabriela Gonzalez-Olvera; Mike W Dunbar; Oselyne Ong; Scott A Ritchie; Thomas S Churcher; et al. (Public Library of Science (PLoS), 2021)
Background In the absence of vaccines or drugs, insecticides are the mainstay of Aedes-borne disease control. Their utility is challenged by the slow deployment of resources, poor community compliance and inadequate household coverage. Novel application methods are required. Methodology and principal findings A 10% w/w metofluthrin "emanator" that passively disseminates insecticide from an impregnated net was evaluated in a randomized trial of 200 houses in Mexico. The devices were introduced at a rate of 1 per room and replaced at 3-week intervals. During each of 7 consecutive deployment cycles, indoor resting mosquitoes were sampled using aspirator collections. Assessments of mosquito landing behaviours were made in a subset of houses. Pre-treatment, there were no differences in Aedes aegypti indices between houses recruited to the control and treatment arms. Immediately after metofluthrin deployment, the entomological indices between the trial arms diverged. Averaged across the trial, there were significant reductions in Abundance Rate Ratios for total Ae. aegypti, female abundance and females that contained blood meals (2.5, 2.4 and 2.3-times fewer mosquitoes respectively; P<0.001). Average efficacy was 60.2% for total adults, 58.3% for females, and 57.2% for blood-fed females. The emanators also reduced mosquito landings by 90% from 12.5 to 1.2 per 10-minute sampling period (P<0.05). Homozygous forms of the pyrethroid resistant kdr alleles V410L, V1016L and F1534C were common in the target mosquito population; found in 39%, 24% and 95% of mosquitoes collected during the trial. Conclusions/significance This is the first randomized control trial to evaluate the entomological impact of any volatile pyrethroid on urban Ae. aegypti. It demonstrates that volatile pyrethroids can have a sustained impact on Ae. aegypti population densities and human-vector contact indoors. These effects occur despite the presence of pyrethroid-resistant alleles in the target population. Formulations like these may have considerable utility for public health vector control responses.